A PILOT STUDY ON THE IMPACT OF ENAM ON FARM PRODUCE MARKETING AND FARMER WELLBEING IN MAHARASHTRA - Pawar, Siddhesh Sadashiv; Walke, Shrikrishna Gulabrao (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The agricultural marketing landscape in India has undergone a significant transformation with the introduction of the Electronic National Agriculture Market (eNAM), aiming to create a unified national market for agricultural commodities. This pilot study investigates the impact of eNAM on farm produce marketing and farmer wellbeing in the state of Maharashtra. By analyzing primary data collected from 150 farmers across three major eNAM-integrated mandis—Pune, Nashik, and Nagpur—the study evaluates key parameters such as market access, price realization, transaction efficiency, digital literacy, and satisfaction levels. The findings reveal a notable increase in average price realization per quintal, greater participation in inter-state trading, and enhanced transparency in price discovery mechanisms post-eNAM adoption. Additionally, the reduction in dependency on intermediaries has led to improved profit margins and a higher sense of empowerment among farmers. However, infrastructural gaps, inconsistent grading and assaying practices, and digital skill disparities remain significant barriers. The study also highlights a positive correlation between eNAM participation and indicators of farmer wellbeing, including financial stability, market confidence, and access to timely market information. Overall, while eNAM presents a promising shift towards digital and inclusive agricultural marketing, its success hinges on the harmonization of state-level reforms, robust infrastructure, and targeted capacity-building interventions. The findings provide valuable insights for policymakers and stakeholders aiming to strengthen digital agricultural ecosystems in India.